Study of the Process of Lubricant Application on the Friction Surface Using Aerosol Lubricators - Voronin, Serhii; Hrunyk, Ivan; Asadov, Bashir; Onopreychuk, Dmytro; Stefanov, Volodymyr (International Journal of Engineering and Technology, 2018)
The problem of calculation and forecasting main parameters of aerosol lubricators designed for applying lubricants on angled to the horizon friction surfaces e.g. the lateral surfaces of a rail and a wheel flange of railway rolling stock is solved in the article.Â The main parameters of lubricators being considered in the article are compressed air supply, the geometry of a spray nozzle and the boundary thickness of a lubricant layer applied to the friction surface where there is no creep of a lubricant under the action of gravity. A structural model of application and retention of a lubricant on a friction surface has been proposed. A mathematical model to calculate main parameters of aerosol lubricators has been developed. The model establishes the connection between the geometry of lubricated friction surfaces, physico-chemical properties of lubricants and the diameter of nozzle aperture and the compressed air supply. The example of calculation of the boundary thickness of a lubricant layer applied to the friction surface under the condition of the absence of its creeping under the action of gravity has been presented in the article. The article presents the results of experimental studies the process of aerosol application of a lubricant to the friction surface. Â